Strategi Green Human Resource Management sebagai Pendukung Transformasi Organisasi di Era Society 5.0 - Melky Retno Pasnijulita Br Hutapea; Khuzaini; Syahrial Shaddiq (Jurnal Riset Multidisiplin Edukasi, 2025)
The Society 5.0 era requires organizations to adapt to technological advancements while maintaining environmental sustainability. One strategic approach to address this challenge is Green Human Resource Management (Green HRM), which emphasizes environmentally friendly practices in managing human resources. This study employs a literature review method by analyzing various scholarly sources on the implementation of Green HRM in supporting organizational transformation. The findings reveal that Green HRM plays a crucial role in establishing an eco-friendly work culture through green recruitment, green training, green performance appraisal, and green compensation. Moreover, the integration of digital technology in the Society 5.0 era enhances the effectiveness of Green HRM implementation, improves operational efficiency, and strengthens organizational reputation. Although challenges such as cultural resistance and limited resources remain, Green HRM continues to serve as a key strategy in achieving organizational sustainability and employee well-being.